Sobre la responsabilidad social empresarial - Rute, José María de la Cuesta (REVISTA PROCESOS DE MERCADO, 2011)
The question of social corporative or business responsibility, a phenomenon internationally known as corporate social responsibility (CSR), deserves consideration on the part of the judicial doctrine as it begins to pierce the legislative process. The reception of the correct social business responsibility doctrine presents itself as especially problematic when businesses exercise influence over a commercial society, single-handedly if it’s from capital company callings. As opposed to the company contractualist thesis, which parallels the private business as a representative in the market, the institutional stamp of CSR affects the conception of the private business and, therefore, on the economic system. Regarding relationships in a company in particular, CSR alternates the relationship between ownership and management, eliminating all traces of a representative relationship between members and administrators; these businesses should secure an evident social interest transcendent to the interest of its own members as soon as they are reunited in the company. On the other hand the attention to proposed goals regarding CSR eliminates the importance of the social object that members propose to reach by means of societal contract. Key words: Responsibility; social responsibility; firm; entrepreneur; trading company; contractualist theory; institutionalist theory; administration and representation; responsibility of the administrators; general meeting; social interest; corporate purpose. JEL Classification: K12, K22, M14. Resumen: La cuestión de la responsabilidad social corporativa o empresarial, fenómeno internacionalmente conocido con las siglas CSR, merece en nuestros días una consideración atenta por parte de la doctrina jurídica e incluso ha llegado a calar en el proceso legislativo. La recepción por el derecho de la doctrina de la responsabilidad social empresarial se presenta como especial - mente problemática cuando la empresa se ejerce por una sociedad mercantil, singularmente si es de las llamadas sociedades de capital. Frente a la tesis contractualista de la sociedad, que es la congruente con la empresa privada como agente en el mercado, el cuño institucionalista de CSR impacta en la concepción de la empresa privada y, por lo tanto, en el sistema de economía de mercado. Particularmente, y por lo que se refiere a la relación de sociedad, CSR altera las relaciones entre propiedad y management, eliminando todo vestigio de relación representativa entre los socios y los administradores; éstos deben velar por un supuesto interés social transcendente al interés de los propios socios en cuanto que reunidos en la sociedad. Por otra parte la atención a metas propuestas en atención a la CSR borra la importancia del objeto social que se proponen los socios alcanzar mediante el contrato de sociedad. Palabras clave: Responsabilidad; responsabilidad social; empresa; empresario; sociedad mercantil; teoría contractualista; teoría institucionalista; administración y representación; responsabilidad de los administradores; junta general; interés social; objeto social. Clasificación JEL: K12, K22, M14.